The impact of internal control, external assurance, and integrated reports on market value. (29th December 2019) - Gal, Graham; Akisik, Orhan
Abstract: It is generally assumed that the credibility of a firm's disclosure is enhanced when there is an independent review. This is the basis for the requirement that an independent audit firm attest to the veracity of financial statements. With the passage of Sarbanes‐Oxley, publicly‐traded North American firms must include a statement about the quality of their internal control system in their financial statements. While the audit of the statements of financial position may be considered to pertain only to that information, the internal control system has a pervasive effect. Therefore, its audit may also impact systems not directly related to financial reporting. Integrated reports combine financial and non‐financial information to provide an overall view of firm's performance. Using data from Compustat North America and GRI, this study shows a positive impact of internal control systems and integrated reports on market value.